Tingkat Motivasi dan Minat Belajar Siswa selama Pandemi Covid-19 di SMPN 27 Bulukumba - Andi Fatmayanti; Tri Susantri (Departement of Mathematics Education, 2023)
This research is quantitative with a descriptive survey research method that aims to collect data and describe an existing symptom, namely the level of motivation and interest in student learning during the Covid-19 pandemic located at SMPN 27 Bulukumba. The sampling technique used is saturated sampling, where the researcher uses the entire population as a sample consisting of 91 students. The data collection technique used is a questionnaire, by applying a self-administered questionnaire. The questionnaire uses a closed statement with a Likert scale measurement procedure with data analysis techniques consisting of the editing stage, data input stage, and tabulation stage. At this stage the data that has been inputted is then calculated the frequency and percentage. The results showed that the level of student motivation and interest in learning during the Covid-19 pandemic at SMPN 27 Bulukumba was low, this was due to limited student learning facilities, changes in the learning system to be brave, and rigid learning that made learning unattractive for students.